2017
DOI: 10.1111/ntwe.12097
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the growth of remote working and its consequences for effort, well‐being and work‐life balance

Abstract: This article critically assesses the assumption that more and more work is being detached from place and that this is a 'winwin' for both employers and employees. Based on an analysis of official labour market data, it finds that only one-third of the increase in remote working can be explained by compositional factors such as movement to the knowledge economy, the growth in flexible employment and organisational responses to the changing demographic make-up of the employed labour force. This suggests that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
469
0
28

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 613 publications
(627 citation statements)
references
References 34 publications
14
469
0
28
Order By: Relevance
“…This finding shows that it is important to take into account how employees influence each other and how they use each other’s skills and knowledge, because these considerations have consequences for individual‐level performance. Our finding is in line with the literature that working from home leads to the intensification of labour (Felstead and Henseke, ), and helps to understand why this is the case (Kelliher and Anderson, ). Because co‐workers are not immediately available, it will take more effort on the part of the individual employee to make use of their skills and knowledge.…”
Section: Conclusion and Discussionsupporting
confidence: 91%
“…This finding shows that it is important to take into account how employees influence each other and how they use each other’s skills and knowledge, because these considerations have consequences for individual‐level performance. Our finding is in line with the literature that working from home leads to the intensification of labour (Felstead and Henseke, ), and helps to understand why this is the case (Kelliher and Anderson, ). Because co‐workers are not immediately available, it will take more effort on the part of the individual employee to make use of their skills and knowledge.…”
Section: Conclusion and Discussionsupporting
confidence: 91%
“…In Sweden, telework has become routine for a sizeable fraction of the population. After decades of slow growth, regular teleworkers now comprise a quarter of all gainfully employed [1,7], and similar tendencies are observed in other Western countries [8][9][10][11]. Research suggests that various factors explain this recent "take-off" [3].…”
Section: Extending Telework: New Groups New Practices and New Technmentioning
confidence: 70%
“…The time and place separations between home and work that exist for office-based workers do not arise as naturally for teleworkers; telework increases the permeability of boundaries between life domains, making it easier for one domain to intrude upon the other (Standen, Daniels, & Lamond, 1999). A study drawing on data from the 2001, 2006 and 2012 Skills and Employment Survey (SES) series found that telework was associated with higher levels of organizational commitment, enthusiasm and job satisfaction; however, it was also associated with working beyond formal working hours, expending voluntary effort, and work-life spillover (Felstead & Henseke, 2017).…”
Section: Well-being: Work-life Balancementioning
confidence: 99%
“…Research has found that the growth of telework statistically surpasses many of the common economic and demographic factors we often ascribe as its drivers. For example, an analysis of trend data from the 1981-2015 Labour Force Series (LFS) surveys found that the increasing trend of work being completed away from a physical workplace far outpaces the growth of the 'knowledge economy', the increase in flexible working arrangements, and demographic shifts in the workforce (Felstead & Henseke, 2017). Therefore this calls for research on telework across a broader spectrum of contextual factors.…”
Section: New Directionsmentioning
confidence: 99%